Foods of Peru - Sheen, Barbara (A taste of culture., 2011)
Explores the foods, cooking traditions, customs, eating habits, and food sources of Peru. Topics include favorite dishes, snacks and sweets, traditional holiday meals, and the preparations and traditions associated with these foods.